2017
DOI: 10.1016/j.bjane.2014.07.015
|View full text |Cite
|
Sign up to set email alerts
|

Intraventricular hemorrhage after dural fistula embolization

Abstract: Intraventricular hemorrhage may be a serious complication after the endovascular treatment of dural arteriovenous fistula. A close postoperative surveillance and monitoring allow an early diagnosis and treatment which increases the odds for an improved outcome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
3
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 24 publications
0
3
0
1
Order By: Relevance
“…Inadvertent embolization of the cavernous and petrosal branches of the middle meningeal artery which triumphantly emerges into the middle cranial fossa through foramen spinosum may precipitate infarctions of the trigeminal and/or facial nerve(9, 14, 21). As to the cavernous sinus DAVFs, the cause of post-hemorrhagic complication was attributed to the venous perforations and hemodynamic changes in cavernous sinus ow constituted the chief causes of post-procedural intracranial hemorrhagic rupture (7,25,26). Among patients harboring pial artery supply, giant venous pouch and high volume Onyx injection in one session constituted the chief causes post-procedural hemorrhagic complications (13).…”
Section: Discussionmentioning
confidence: 99%
“…Inadvertent embolization of the cavernous and petrosal branches of the middle meningeal artery which triumphantly emerges into the middle cranial fossa through foramen spinosum may precipitate infarctions of the trigeminal and/or facial nerve(9, 14, 21). As to the cavernous sinus DAVFs, the cause of post-hemorrhagic complication was attributed to the venous perforations and hemodynamic changes in cavernous sinus ow constituted the chief causes of post-procedural intracranial hemorrhagic rupture (7,25,26). Among patients harboring pial artery supply, giant venous pouch and high volume Onyx injection in one session constituted the chief causes post-procedural hemorrhagic complications (13).…”
Section: Discussionmentioning
confidence: 99%
“…Alguns materiais podem ser utilizados na embolização, tais como Onyx e n-butilcianoacrilato. Nesse relato de caso, foi utilizado para a embolização da FAVDS o material Onyx, um agente embólico não adesivo, composto por etileno e álcool vinílico dissolvido em dimetilsulfóxido 6 . Artigos recentes demonstraram que a técnica endovascular utilizando Onyx tem algumas vantagens sobre o cianoacrilato, incluindo um maior controle do processo embólico do agente durante a injeção e tempo de injeção com poucas complicações 7 .…”
Section: Discussionunclassified
“…Lee et al 5 reported that partial obliteration of the drainage pathways resulted in cerebellar edema and hemorrhage due to high intracavernous sinus pressure and residual dangerous cortical venous drainage. De Carvalho et al 6 reported one case of intraventricular hemorrhage after dural fistula embolization due to occlusion of its venous drainage. Similar cases of complications have been reported in the literature.…”
Section: Discussionmentioning
confidence: 99%
“…De Carvalho et al. 6 reported one case of intraventricular hemorrhage after dural fistula embolization due to occlusion of its venous drainage. Similar cases of complications have been reported in the literature.…”
Section: Discussionmentioning
confidence: 99%